Implementing Religious Activity Programs in Madrasah Tsanawiyah to Develop Students’ Emotional Intelligence and Discipline - Aini, Nurul; Noviani, Dwi; Sholihah, Virdatus (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This This study aims to describe the implementation of religious activity programs in Islamic junior high schools (Madrasah Tsanawiyah) in developing students’ emotional intelligence and discipline. Religious activities such as shalat dhuha, tahfiz al-Qur’an, muhadharah, and mabit are integral parts of character education based on Islamic spiritual values. Through these activities, students are trained not only in cognitive and spiritual aspects but also in emotional control, responsibility, and discipline in fulfilling their obligations. This research employs a descriptive qualitative approach, using observation, interviews, and documentation as data collection techniques. The results indicate that religious activities significantly contribute to improving students’ emotional intelligence, as reflected in their ability to control emotions, respect others, and remain calm in facing challenges. Furthermore, students’ discipline increases through the structured and continuous routines of religious programs. Therefore, the implementation of religious activities in Madrasah Tsanawiyah is proven effective in fostering students’ religious, emotional, and disciplinary character formation.